1992 Summer School in High Energy Physics and Cosmology Trieste, Italy, 15 June-31 July, 1992 (The ICTP series in theoretical physics, 1993)
"The material presented at the 1992 school falls in two parts. Part I covered areas involving Topological Gauge Theories, Two-dimensional gravity, Integrable models and several other aspects of string theories. The last three days were devoted to a Workshop covering recent developments in this rapidly evolving field. The second part (II) of the school covered many of the leading areas in phenomenologi<;al high energy physics as well as cosmology. Topics included Neutrino physics, Supersymmetry, Non-perturbative Aspects of the Standard Electroweak Model, Inflation and Topological Defects. The latest experimental results from LEP as well as the Cosmic Background Explorer (COB E) werealso covered."--Preface